Passenger Satisfaction Analysis on Bekasi Station Service Performance - Widodo Budi Dermawan; Fadli Bimantara; Muhammad Isradi; Amar Mufhidin (NAROTAMA UNIVERSITY, Indonesia)
Bekasi Station (BKS) is a large class C train station located on Jl. H. Juanda, Bekasi City at an altitude of +19 meters, including in Operation Area I Jakarta. This station serves thousands of commuter passengers to Jakarta and surrounding areas by KRL Commuter Line and there is a KRL depot to the west of the station. Bekasi Station is quite crowded. Therefore, it is very important to know how the current condition of Bekasi Station and the level of satisfaction of train service users to the performance of Bekasi Station services. This study uses Importance Performance Analysis (IPA) method and field survey method to conduct direct observations at the station to evaluate the condition of Bekasi Station which will be compared with Regulation of the Minister of Transportation No. PM 48 of 2015 concerning Minimum Service Standards for Transportation of People By Train at Stations. As well as the Regulation of the Minister of Transportation No. 29 of 2011 concerning the technical requirements of railway station building. Then to know about the performance of the service and the satisfaction of the passengers, it is necessary to spread the questionnaire. The results of the evaluation showed that the needs of the building area of basic activities and the width of the platform still meet the standards of the existing rules in the Regulation of the Minister of Transportation No. 29 of 2011. The average level of passenger satisfaction to the service and facilities of Bekasi Station is satisfied with the average performance level of the station which is good with an average score of 4.04 and an average - the average level of station performance is good with an average score of 4.05 from the highest score of 5.